Brief Report: Performance of Tuberculosis Symptom Screening Among Hospitalized ART-Naive Children With HIV in Kenya. (1st November 2022) - Cranmer, Lisa M.; Njuguna, Irene N.; LaCourse, Sylvia M.; Figueroa, Janet; Gillespie, Scott; Maleche-Obimbo, Elizabeth; Otieno, Vincent; Mugo, Cyrus; Okinyi, Helen; Benki-Nugent, Sarah; Pavlinac, Patricia B.; Malik, Amyn A.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The World Health Organization (WHO) recommends tuberculosis (TB) diagnostic evaluation for children with HIV (CHIV) who have history of TB contact, poor weight gain, cough, or fever. These screening criteria were developed based on studies of symptomatic CHIV with incomplete microbiologic confirmation. We performed routine TB microbiologic evaluation of hospitalized CHIV with and without symptoms to develop a data-driven TB symptom screen. Methods: Among hospitalized antiretroviral therapy–naive Kenyan CHIV enrolled in the Pediatric Urgent Start of Highly Active Antiretroviral Therapy (PUSH) trial, we performed Xpert MTB/RIF and mycobacterial culture of respiratory and stool specimens independent of TB symptoms. We evaluated performance of WHO and other published pediatric TB screening criteria and derived optimized criteria using a combination of symptoms. Results: Of 168 CHIV who underwent TB microbiologic evaluation, 13 (8%) had confirmed TB. WHO TB symptom screening had 100% sensitivity and 4% specificity to detect confirmed TB. Published TB screening criteria that relied on prolonged symptoms missed cases of confirmed TB (sensitivity 85%–92%). An optimized symptom screen including weight loss, cough, anorexia, or TB contact had 100% sensitivity and improved specificity (31%) compared with the WHO pediatric TB symptom screen. Conclusions: The WHO TB symptom screen was highly sensitive but resulted in a high proportion of hospitalized CHIV who would require TB diagnostic evaluation. Other published TB screening criteria missed CHIV with confirmed TB. Our optimized screening tool increased specificity while preserving sensitivity. Future multicenter studies are needed to improve TB screening tools for CHIV in both inpatient and outpatient settings.